2003
DOI: 10.1002/gcc.10297
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation and overexpression of HMGA2 in myelofibrosis with myeloid metaplasia

Abstract: Among cytogenetic studies of patients affected with myelofibrosis with myeloid metaplasia (MMM), a rare chronic myeloproliferative disorder, we found several reports of structural abnormalities of the long arm of chromosome 12. Two MMM patients had a balanced translocation involving 12q: t(4;12)(q32;q15) and t(5;12)(p14;q15), respectively. FISH (fluorescence in situ hybridization) analysis showed that BAC (bacterial artificial chromosome) RP11-366L20 overlaps the breakpoint in both cases. A gene, HMGA2, most o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
35
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 27 publications
2
35
0
3
Order By: Relevance
“…In the literature, Andrieux et al 7 reported a possible role in the association between HMGA2 and translocation involving 12q15 in CIMF. In the current study, we found that 12q15 anomaly does not depend on the JAK2 mutational status; thus genetic anomaly, independent to JAK2 V617F , may exist in CIMF, and molecular study on the 12q15 region, including HMGA2, 8 may disclose another pathogenetic pathway in CIMF.…”
Section: Figurementioning
confidence: 99%
“…In the literature, Andrieux et al 7 reported a possible role in the association between HMGA2 and translocation involving 12q15 in CIMF. In the current study, we found that 12q15 anomaly does not depend on the JAK2 mutational status; thus genetic anomaly, independent to JAK2 V617F , may exist in CIMF, and molecular study on the 12q15 region, including HMGA2, 8 may disclose another pathogenetic pathway in CIMF.…”
Section: Figurementioning
confidence: 99%
“…Despite the diversity of chromosomal translocations in patients with leukemia or lymphoma, direct involvement of HMGA2 has only been reported in four cases, one with Richter transformation of chronic lymphocytic leukemia (CLL), 35 one with acute lymphoblastic leukemia (ALL) 27 and two with myelofibrosis with myeloid metaplasia (MM). 28 Here, we report six cases of myeloid malignancy with reciprocal translocations involving 12q13-15 and involvement of HMGA2.…”
mentioning
confidence: 91%
“…8,26 These mRNA variants have been found in all the tumor types described above. 8,[26][27][28][29] These findings, and the fact that there is no obvious functional relationship between the various partner genes, suggest that overexpression of the N-terminal part of HMGA2 may be the critical transforming event in tumors with 12q13 rearrangements, rather than the formation of particular fusion genes. This idea is supported by functional analysis using both cell lines and animal models.…”
mentioning
confidence: 99%
“…In some of them, the partner gene in translocation (or inversion) was identified, although 3 0 RACE-PCR analysis excluded the possibility of a fusion transcript. 6,7 In some of them, aberrant truncated forms of HMGA2 transcripts were described as containing exons 1-3 and a sequence from intron 3 or intron 2, 7 leading to truncation of the acidic carboxyl domain of the protein. 6,7 HMGA2 activation has been reported in myelodysplasia 7 and myelofibrosis with myeloid metaplasia, 6 but never in PV.…”
mentioning
confidence: 99%
“…6,7 In some of them, aberrant truncated forms of HMGA2 transcripts were described as containing exons 1-3 and a sequence from intron 3 or intron 2, 7 leading to truncation of the acidic carboxyl domain of the protein. 6,7 HMGA2 activation has been reported in myelodysplasia 7 and myelofibrosis with myeloid metaplasia, 6 but never in PV. Reverse transcription (RT)-PCR and 3 0 RACE-PCR excluded the formation of a 5 0 HMGA2/3 0 TNIK chimeric transcript and, moreover, no difference in the transcriptional pattern of the TNIK gene was observed among PV patients (Figure 1g).…”
mentioning
confidence: 99%